British recoveries of Mallard ringed at Borough Fen Decoy, Northamptonshire - Ogilvie, M A; Cook, W A (Wildfowl, 1972)
British recoveries of Mallard Anas platyrhynchos ringed at Borough Fen Decoy, Northamptonshire, have been analysed. A corrected same season recovery rate is used to calculate season of ringing mortality rates which form an effective way of monitoring annual variations immediately after the end of each shooting season. The natural mortality rate for this population of Mallard, if there were no shooting, would be about 20% per annum. The season of ringing mortality rate has varied between 39.3% and 61.8%, the latter in the severe winter of 1962-63. The number of birds ringed each season does not seem to have any relationship with the annual breeding success as measured by the percentage of adults in the catch, or with the size of the population measured by counts on waters within 80 miles (128 km.) of Borough Fen. There has not been any falling off in the reporting rate of recoveries, even close to the ringing station. The distribution of recoveries round the Decoy follows topographical features favourable to Mallard. The present scale of Mallard ringing at the Decoy is only just adequate to provide the necessary number of recoveries for annual analysis.